2020
DOI: 10.1097/meg.0000000000001793
|View full text |Cite
|
Sign up to set email alerts
|

Single-step endoscopic ultrasound-guided multiple gateway drainage of complex walled-off necrosis with lumen apposing metal stents

Abstract: In this study we analyzed the feasibility and safety of single-step multiple transluminal gateway drainage (MTGD) for complex walled-off necrosis (WON) using lumen-apposing metal stents (LAMSs). Six patients underwent endoscopic ultrasound (EUS)-guided MTGD using two LAMSs. Technical success was 100%. The mean procedure time was 29 min. The mean number of direct endoscopic necrosectomy sessions per patient was 2. Two of six patients developed adverse events, which was bleeding in both cases and treated endosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Furthermore, the availability of LAMS of different caliber (up to 20 mm), allows one to adapt the treatment to the characteristics of the wall and the content of the collection, even when composed of solid necrotic material [49]. Recent trials also demonstrated how the apposition of multiple stents in different sites, especially when dealing with large and multiloculated PNCs, facilitates the drainage of the collections, even though using LAMS reduces the need to use the MTGT when compared to PSs [50]. A recent cost-effectiveness analysis also showed how, despite being more expensive, LAMSs are more cost-effective compared to PSs [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the availability of LAMS of different caliber (up to 20 mm), allows one to adapt the treatment to the characteristics of the wall and the content of the collection, even when composed of solid necrotic material [49]. Recent trials also demonstrated how the apposition of multiple stents in different sites, especially when dealing with large and multiloculated PNCs, facilitates the drainage of the collections, even though using LAMS reduces the need to use the MTGT when compared to PSs [50]. A recent cost-effectiveness analysis also showed how, despite being more expensive, LAMSs are more cost-effective compared to PSs [55].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, comparing the 15-and 20-mm EC-LAMS, Parsa et al reported that fewer DEN sessions are needed to reach WOPN resolution when using the 20 mm EC-LAMS [44] and Bekkali et al found that the use of EC-LAMS was associated with a reduced procedure time when compared with a first-generation LAMS in drainage and DEN [50]. Binda et al demonstrated how MTGT can also be safely and efficaciously carried out with EC-LAMS for treating complex WOPN [50].…”
Section: Clinical Practice With Lamssmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Bang et al presented a successful case of MTGT using Axios stents. Using the single-step creation of tracts with Axios stents, MTGT has the potential to become essential to the framework of endoscopic management of WOPN [59][60][61]. However, larger, randomized studies are needed to validate these findings as limited studies are currently available.…”
Section: Multiple Transluminal Gateway Techniquementioning
confidence: 99%
“…Apart from the endoscopic approach, combined endoscopic-percutaneous approaches are recommended, especially in cases where the collection extended beyond endoscopic reach [14]. Moreover, having multiple endoscopes in different locations, the so-called "multigateway approach," is employed to maximize the drainage ability by using either multiple plastic stents [15] or multiple LAMS [16]. In cases with multiple subcavities, multiple plastic stents could be placed between the gastric lumen and small cavity through the connection with the main cavity [17].…”
Section: Endoscopic Step-up Approachmentioning
confidence: 99%